SOSIALISASI PENGEMBANGAN MEDIA DALAM PEMANFAATAN TV DIGITAL DI DESA BANYUMAS - April Laksana; Rizqi Fitrianti; Ali Humadi (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
In the development of technology in the era of globalization of the world, there are many developments of technology media and the migration of transitions from analog TV to digital TV communications that occur in this life. When time went by so fast after the impact of Covid-19 which was able to cripple the community's economy as well as a large social impact on the wider community, because a change in habits that started as normal became abnormal in social life so that everything turned into a new life (New Normal) by following changing times and forced to be ready to face a new life by innovating change by migrating to social media and digital technology. In order for the dissemination of media development in the use of digital tv in the village of Banyumas, where annual activities are usually held by Universities in Banten Province by conducting academic activities holding Student Work Lectures (KKM) conducted by Bina Bangsa University (UNIBA). A community service activity in the form of the University's tridharma, namely education, service, and research. As well as in the form of dedication carried out by a student to be able to develop media in the community, for the progress of a village that is indeed far from the touch of media and the benefits of digital technology